FINANCIAL RATIOS IMPACT ON SOE CONTAINER COMPANIES FINANCIAL DISTRESS - Isfahan, Saif Raafi'in; Syahputri, Anggraini; Malini, Helma; Azazi, Anwar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study uses asset tangibility as a mediating variable to examine the impact of liquidity, firm size, and profitability ratios on financial distress in Indonesian state-owned Container companies. The study runs from 2019 to 2023. The study applies multiple linear regression analysis on 14 state-owned Container companies listed on the Indonesia Stock Exchange. The Altman Z-score model is used to assess financial distress, with independent variables including the current ratio (liquidity), natural log of total assets (firm size), return on assets (profitability), and net tangible assets (asset tangibility). The study looks into direct impacts, mediating linkages, and interaction effects between variables. The result stated that profitability has directly affected financial distress and asset tangibility hasn’t directly affected financial distress and hasn’t meditated independent variables toward financial distress. Lastly, there are interaction effects of a combination of independent and meditating variables toward the dependent variable. This study recommends that Indonesian state-owned on container sector companies focus on three key areas to prevent financial distress: implementing robust liquidity monitoring systems with early warning mechanisms and clear guidelines for cash management, developing comprehensive asset management policies including regular maintenance and assessment, and establishing specific targets and cost optimization strategies. These measures are essential for maintaining financial stability and preventing distress in these container sector.